The globalization of world politics - Baylis, John, 1946-; Smith, Steve, 1952-; Owens, Patricia, 1975- (Oxford : Oxford University Press, 2023)
"In this new edition of The Globalization of World Politics we have followed a similar format and structure to previous editions, but we have added one new chapter and one chapter has been completely rewritten by a new author. We believe these additions make this already popular and successful book even better. A new chapter on global health by Sophie Harman has been included because of the contemporary importance of the Covid-19 pandemic and its effects on international relations. The chapter on realism by Or Rosenboim provides a new perspective on this important theoretical approach to the subject. All the other chapters have been updated to reflect the feedback we have received from students from around the world, comments from teachers and scholars of International Relations, and the extremely detailed reviews of the eighth edition commissioned by Oxford University Press. Together, all these comments have helped us to identify additional areas that should be covered. We have also updated the learning features, including dozens of brand-new case studies and many new suggestions for further reading"--
Includes bibliographical references (pages 559-596) and index.
Keywords: International relations -- Textbooks; World politics -- Textbooks; Globalization -- Textbooks